Courtesans, bar girls & dancing boys : the illicit worlds of Indian dance - Morcom, Anna (Hachette Book publishing India Pvt ltd, 2014)
This is a remarkable book, of great originality, rigour, and importance in the study of modern Indian popular culture. Combining extensive fieldwork, archival research, and astute interpretation, Morcom presents a rich exploration of the contradictory effects of modernity, nationalism, and bourgeois values on a diverse range of Indian dance traditions, old and new.’ — Peter Manuel, Professor, Graduate Center of the City University of New York ‘Anna Morcom’s extraordinarily compelling book represents one of the most significant interventions in the study of dance in contemporary South Asia. Masterfully bridging discourses on class, gender, globalisation, economics, morality, and aesthetics, it effectively foregrounds the forms of inequality and power at work in the production, consumption, and politicisation of dance in today’s India.’ — Davesh Soneji, McGill University, author of Unfinished Gestures: Devadasis, Memory and Modernity in South India ‘A hugely valuable addition to the literature on the performing arts in India, focusing as it does on communities of highly marginalised dancers who have received scant academic attention. Illicit Worlds of Indian Dance deals with a wide-ranging set of dance sectors including female hereditary performers, bar dancers, transgender erotic performers and kothi dancers, interpreting the author’s rich ethnographic detail through a variety of theoretical lenses. On all counts, a very welcome and timely scholarly contribution.’ — Prabha Kotiswaran, author of Dangerous Sex, Invisible Labor: Sex Work and the Law in India ‘This fascinating investigation of the hidden hereditary communities of female and transgender dancers in contemporary India compels us to rethink our assumptions about Indian public culture, sexualities, and entertainment. Expertly moving between colonial and postcolonial discourses on these communities, Anna Morcom reveals the ways in which postcolonial nation-building in the name of progress and modernity has excluded a range of non-elite subjectivities and marginalised their role as carriers of embodied culture. Morcom’s book not only chronicles their complex relationships with mainstream society and legitimate performing arts (including Bollywood), their legal struggles, and their talents, but, in doing so, offers a compassionate and timely valourisation of these illicit and yet ever-present worlds.’ — Ananya Jahanara Kabir, Professor, King’s College London, and author of Territory of Desire: Representing the Valley of Kashmir Until the 1930s no woman could perform in public and retain respectability in India. Professional female performers were courtesans and dancing girls who lived beyond the confines of marriage, but were often powerful figures in social and cultural life. Women’s roles were often also taken by boys and men, some of whom were simply female impersonators, others transgender. Since the late nineteenth century the status, livelihood and identity of these performers have all diminished, with the result that many of them have become involved in sexual transactions and sexualised performances. Meanwhile, upper-class, upper-caste women have taken control of the classical performing arts and also entered the film industry, while a Bollywood dance and fitness craze has recently swept middle class India. In her historical and on-the-ground study, Anna Morcom investigates the emergence of illicit worlds of dance in the shadow of India’s official performing arts. She explores over a century of marginalisation of courtesans, dancing girls, bar girls and transgender performers, and describes their lives as they struggle with stigmatisation, derision and loss of livelihood.